Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

please help me to find out the inverse this function,
$$f(x)=\frac{e^x+e^{-x}}{e^x-e^{-x}}$$ I know that, let
$$y=\frac{e^{x}+e^{-x}}{e^{x}-e^{-x}}$$ and if I find $x=\cdots$ then that is the inverse. But I can't calculate this. Is this the only way. is there any other way to figure it out?

share|cite|improve this question
    
This is the hyperbolic cotangent function, and its inverse is the inverse hyperbolic cotangent function. – Ayesha Feb 9 '14 at 3:21
    
Replace $e^x$ with some other letter, say, $u$; notice that $e^{-x}$ is just $1/u$; now you have a formula for $y$ in terms of $u$; can you solve that formula for $u$? – Gerry Myerson Feb 9 '14 at 5:20

Applying Componendo and dividendo on $$\frac y1=\frac{e^{x}+e^{-x}}{e^{x}-e^{-x}},$$

we get

$$\frac{y+1}{y-1}=\frac{e^x}{e^{-x}}=e^{2x}$$

$$2x=\ln\left(\frac{y+1}{y-1}\right)$$

share|cite|improve this answer
    
Where did that absolute value come from? If $e^{2x}=\dfrac{y+1}{y-1}$ then $2x = \ln\dfrac{y+1}{y-1}$. ${}\qquad{}$ – Michael Hardy Feb 9 '14 at 5:27
    
@MichaelHardy,sorry for the wrong notation. – lab bhattacharjee Feb 9 '14 at 5:45

You have $$ y = \frac{e^x+e^{-x}}{e^x-e^{-x}}. $$ Multiplying the top and bottom by $e^x$, you get $$ y = \frac{e^{2x}+1}{e^{2x}-1}. $$ The advantage of this form is that $x$ now appears ONLY within the expression $e^{2x}$, so we can treat $e^{2x}$ as the unknown that we're trying to solve for.

Now clearing fractions, we get $$ (e^{2x}-1)y = e^{2x}+1 $$ so $$ e^{2x}y - y = e^{2x}+1 $$ and then $$ e^{2x}y -e^{2x} = y+1. $$ From this we get $$ e^{2x}(y-1) = y+1. $$ Then $$ e^{2x} = \frac{y+1}{y-1}, $$ $$ 2x = \ln \frac{y+1}{y-1}, $$ $$ x = \frac 1 2 \ln \frac{y+1}{y-1}. $$

share|cite|improve this answer

$$ f(x) = \frac{e^x+e^{-x}}{e^x-e^{-x}} = \frac{2\cosh(x)}{2\sinh(x)} = \frac{1}{\tanh(x)} = \coth(x) $$

therefore,

$$ f^{-1}(x)= \operatorname{arccoth}(x) $$

share|cite|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.